Study of reproduction cycles and yield dynamics of the classical swine fever virus in PK-15 cultured cells using a fluorescent probes technique - Reshetniak, L.D.; Krasnobayev, E.A.; Novozhilova, E.V.; Zherebtsova, E.N.; Popova, G.A. (Биополимеры и клетка, 2000)
The authors have elaborated some methodological approaches necessary to solve certain biotechnological problems. This approaches permit to study the classical swine fever virus reproduction and accumulation in a swine established cell line, PK-15, the virus propagation being accompanied with no cytopathic effect. The reliable and promising fluorescent probe technique needing no previous virus adaptation and multiplication in permissive cells is successfully confirmed to be useful for such purposes. Розроблено важливу для вирішення біотехнологічних проблем методологію вивчення циклів розмноження та динаміки накопичення вірусу класичної чуми свиней в культурі перевивних клітин РК-15 за умов відсутності будь-яких проявів цитопатогенної дії вірусу. Підтверджено можливість широко використання з цією метою перспективного та надійного методу флюоресцентных зондів, що не потребує попередньої адаптації інфекційного чинника до чутливої культури та подальшого його розмноження в чутливих клітинах. Разработана важная для решения биотехнологических проблем методология изучения циклов размножения и динамики накопления вируса классической чумы свиней в культуре перевиваемых клеток РК-15 в условиях, когда отсутствуют какие-либо проявления цитопатического действия вируса. Подтверждена возможность широкого использования с этой целью перспективного и надежного метода флюоресцентных зондов, не требующего предварительной адаптации инфекционного агента к чувствительной культуре и последующего его размножения в чувствительных клетках.